Association of ambulatory heart rate and atherosclerosis risk factors with blood pressure in young non-hypertensive adults. Issue 1 (12th February 2016) - Cheng, Cynthia; Daskalakis, Constantine
Abstract : Objective: The study objective was to assess the association between 24 h ambulatory heart rate (HR), atherosclerosis risk factors and blood pressure (BP) in young non-hypertensive patients. Methods: We recruited 186 participants aged 18–45 years from a large urban academic Family Medicine outpatient practice, serving 40 000 individuals for this observational study. The main analyses were based on multiple linear regression, with mean 24 h BP (systolic BP (SBP) or diastolic BP (DBP)) as the outcomes, mean 24 h HR as the main predictor of interest, and controlling for age, gender, race, insulin sensitivity/resistance and endothelial function measured by strain gauge venous occlusion plethysmography. Results: HR was independently associated with mean 24 h SBP and DBP (SBP and DBP: p=0.042 and 0.001, respectively). In our analyses, associations were markedly stronger for ambulatory compared with office BP measurements. Endothelial dysfunction was associated with higher SBP (p=0.013); plasminogen activator inhibitor-1 was significantly associated with both SBP and DBP (p=0.041 and 0.015, respectively), while insulin resistance was not associated with either SBP or DBP. Insulin resistance and C reactive protein were significant predictors of HR (p=0.013 and 0.007, respectively). Conclusions: These findings suggest that HR may be a potential marker of elevated cardiovascular risk in young asymptomatic individuals, prior to the development of clinical hypertension or cardiovascular disease.